A civil law for the age of precedents? a look into Brazilian adjudication - Reschke, Pedro Henrique (Civil Procedure Review, 2020)
This paper is an attempt to understand why Brazilian legal theorists, specially civil procedure scholars, have suddenly become to talk so much about precedent. It is also an attempt to see whether their studies are theoretically sound. First, I try to identify what is the problem that precedent is seen as the solution to. Next, I talk about how Brazil developed its own model of precedent, and then compare it to the theory of precedent as it developed in common law systems, concluding that the Brazilian system still has a lot to learn before being able to create a proper, fair and democratic system of legal precedent.